Prevalence of “Persistent Low Grade Morbidities” in a Section of Urban Youth Population - Syed Arshad Sabir, Imrana Aslam , Laraib Khatoon ,Zuneera Shabbir ,Amna Sohail Kamran Bashir Khan, Syed Arshad Sabir, Imrana Aslam , Laraib Khatoon ,Zuneera Shabbir ,Amna Sohail Kamran Bashir Khan (Journal of Rawalpindi Medical College, 2017)
To determine the frequency and pattern of persistent low grade morbidities (PLGMs) in youth and also to identify life style factors which may influence their occurrence. Methods: In this cross-sectional study 200 younger urban people (19-24Y) were inquired by a self designed questionnaire by direct interviewing. Results: Mean age was 21years. Sixty four percent were female, 69% students, 6.5% smokers and 90.5% were unmarried. Distribution of PLGMs found was depressive mood swings(62%), frequent headache (46.5%), pain in lower limbs (44.5%), neck shoulder & back pain (44%) , easy fatiguability (42.5%), difficulty in falling asleep (38%) and epigastric discomfort (28%). More females (64.04%) were found affected. Statistically important co-variations between healthy behaviours and the absence of selected PLGMs (OR=1.01 – 2.09) was seen. Conclusions: Study findings are close to presumptions and are enough to sensitize relevant public health stake holders for needed measures. Clinical studies would help to find the ultimate causes of morbid states in focus